An Animated videos based on Tajweed science to improve students' ability to read the Al-Qur'an - Nasrul, Nasrul; Gani, Hamsu Abdul; Hakim, Abdul (Journal of Research in Instructional, 2024)
Tajweed learning videos are made to help students become more proficient in reading the Al-Qur'an. This study aims to develop an animated video based on valid, practical, and effective Tajweed science to improve elementary school students' ability to read the Al-Qur'an. The research used the ADDIE research and development model. The study subjects were 24 fifth-grade students of Al-Qur'an Wahdah Islamiyah 02 Makassar Elementary School. Data were collected through observation, questionnaires, and interviews. Data were analyzed using descriptive statistical analysis and qualitative descriptive analysis. The study has produced an animated video media based on Tajweed science. Based on the results of the analysis of media development needs, it is at the percentage needed, and from the results of interviews with students regarding understanding the material, it was found that students had not received more material related to Tajweed science. The animated video developed has met the criteria of valid based on material experts (89%) and media experts (93%), practical based on student responses (90) and teachers (92.70), and can improve the ability to read the Al-Qur'an of elementary school students (pretest = 58.8, posttest 93.5). This study concludes that animated videos based on Tajweed science have met the valid, practical, and effective criteria in improving elementary school students' ability to read the Al-Qur'an.